Aplikasi Drone Wawasan Tani untuk Pertanian di Simpang Lima, Sungai Besar, Selangor - Nuri Ikhwana; Dwi Retno Hapsari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
The main points of agricultural development include technology that is constantly developing. Utilization of technology today makes agriculture can increasingly develop effectively and be able to compete with market prices in the modern era. Drone for spraying fertilizer is one of the technologies applied by the area around the Wawasan Tani Cooperative, Simpang Lima, Sungai Besar, Selangor. This community service aims to determine the application of drones in agriculture and decision making on the application of Farmer Insights Drone. This service method uses qualitative data in the form of primary data from interviews and field observations as well as secondary from journal literature and books. Based on the data, the Farmers' Insights drone has been successfully applied by 70% of people in this region. Some people are not aware of this innovation because access to information has not yet reached the entire community. This innovation will continue to be expanded as a form of the role of cooperatives in protecting the community.